Natural experiment to measure change in energy use and indoor environment in dwellings with smart heat pump retrofits - Zahiri, S; Gupta, R; Hampton, S (European Council for an Energy Efficient Economy, 2021)
The UK Government announced in 2020 its ‘Ten Point Plan’ for a green industrial revolution, which includes a challenging target to install 600,000 heat pumps per year by 2028. Balancing electricity supply and demand locally is key to the success of achieving this target.